Strongyloides ratti: implication of mast cell-mediated expulsion through FcεRI-independent mechanisms - Watanabe K.; Kishihara K.; Hamano S.; Koga M.; Nomoto K.; Tada I. (Parasite, 2009)
In order to examine whether FcεRI-dependent degranulation of intestinal mast cells is required for expulsion of intestinal nematode Strongyloides ratti, CD45 exon6-deficient (CD45-/-) mice were inoculated with S. ratti. In CD45-/- mice, egg excretion in feces persisted for more than 30 days following S. ratti larvae inoculation, whereas in wild-type (CD45+/+) mice, the eggs completely disappeared by day 20 post-infection. The number of intestinal mucosal mast cells, which are known effector cells for the expulsion of S. ratti, was 75% lower in CD45-/- mice compared with that in CD45+/+ mice. Adoptive transfer of wild-type T cells from CD45+/+ mice into CD45-/- mice reduced the duration of S. ratti infection to comparable levels observed in CD45+/+ mice, with concomitant increases in intestinal mucosal mast cells. These results showed that CD45 is not involved in the effector function of intestinal mucosal mast cells against S. ratti infection. Since FcεRI-dependent degranulation of mast cells is completely impaired in these CD45 knockout mice, we conclude that FcεRIdependent degranulation is not required in the protective function of intestinal mucosal mast cells against primary infection of S. ratti.